Atherosclerotic Cardiovascular Disease in Gulf War Veterans in Relation to Deployment Exposures - Sarah T. Ahmed; Ruosha Li; Lea Steele; Peter Richardson; Kellie Sims; Rachel Quaden; Kelly M. Harrington; Vijay Nambi; John M. Gaziano; Robert Morgan; George L. Delclos; Drew A. Helmer (Cardiovascular Toxicology, 2025)
Many 1990–1991 Gulf War Veterans (GWVs) were exposed to toxicants and environmental hazards during deployment, including oil well fire smoke, chemical/biological agents, pyridostigmine bromide (PB) pills, and pesticides. Multiple constituents of smoke are associated with increased risk for atherosclerotic cardiovascular diseases (ASCVD), and other toxic exposures have been associated with autonomic and lipid dysfunction. We used data from the Gulf War Era Cohort and Biorepository Study of veterans deployed to Gulf War in 1990–1991 ( n = 942). We evaluated the association of deployment exposures (no, yes (1–6 days), (7–30 days), (31 + days), and not sure) with clinical risk factors (hypertension, diabetes, high cholesterol) and ASCVD using multivariable logistic regression. We adjusted for all clinical risk factors in the models to test the association of military exposures and ASCVD. We found that 7–30 days exposure to oil well fire smoke (OR: 2.95, CI: 1.40, 6.19), PB pills (OR: 2.37, CI: 1.06, 5.32), and chemical/biological agents (OR: 3.60, CI: 1.04, 12.51) were associated with ASCVD. Exposure to chemical/biological agents for 7–30 days was also associated with hypertension (OR: 4.18, CI: 1.48, 11.86) and for 31 + days was associated with ASCVD (OR: 4.24, CI:1.20, 14.94). The associations between oil well fire smoke and chemical/biological agents with ASCVD remained significant in models adjusting for clinical risk factors. For GWVs, exposure to oil well fire smoke, chemical/biological agents, and PB pills were associated with ASCVD. These exposures may represent population-specific risk enhancers for ASCVD and may be considered in individualized clinical risk assessment.